Sendai virus recombinant vaccine expressing hPIV-3 HN or F elicits protective immunity and combines with a second recombinant to prevent hPIV-1, hPIV-3 and RSV infections - Zhan, Xiaoyan (2008)
The human parainfluenza viruses (hPIVs) and Respiratory Syncytial Virus (RSV) are the leading causes of serious respiratory illness in the human pediatric population. Despite decades of research, there are currently no licensed vaccines for either the hPIV or RSV pathogens. Here we describe the testing of hPIV-3 and RSV candidate vaccines using Sendai virus (SeV, murine PIV-1) as a vector. SeV was selected as the vaccine backbone, because it has been shown to elicit robust and durable immune activities in animal studies, and has already advanced to human safety trials as a xenogenic vaccine for hPIV-1. Two new SeV-based hPIV-3 vaccine candidates were first generated by inserting either the fusion (F) gene or hemagglutinin-neuraminidase (HN) gene from hPIV-3 into SeV. The resultant rSeV-hPIV3-F and rSeV-hPIV3-HN vaccines expressed their inserted hPIV-3 genes upon infection. The inoculation of either vaccine into cotton rats elicited binding and neutralizing antibody activities, as well as interferon-γ-producing T-cells. Vaccination of cotton rats resulted in protection against subsequent challenges with either homologous or heterologous hPIV-3. Furthermore, vaccination of cotton rats with a mixture of rSeV-hPIV3-HN and a previously described recombinant SeV expressing the F protein of RSV resulted in protection against three different challenge viruses: hPIV-3, hPIV-1 and RSV. Results encourage the continued development of the candidate recombinant SeV vaccines to combat serious respiratory infections of children.